Development of an engineering methodology for non-linear fracture analysis of impact-damaged pressurized spacecraft structures - Igor Telichev (Fracture and Structural Integrity)
Motivated by the dramatic worsening and uncertainty of orbital debris situation, the present paper is focused on the structural integrity of the spacecraft pressurized modules/pressure vessels. The objective is to develop an engineering methodology for non-linear fracture analysis of pressure wall damaged by orbital debris impact. This methodology is viewed as a key element in the survivability-driven spacecraft design procedure providing that under no circumstances will the “unzipping” occur. The analysis employs the method of singular integral equation to study the burst conditions of habitable modules, although smaller vessels containing gases at higher pressures can also be analyzed.